Laccase‐mediated grafting of polyphenols onto cationized cotton fibers to impart UV protection and antioxidant activities. Issue 6 (5th October 2017) - Kim, Suyeon; Lee, Hyunkyung; Kim, Juhea; Oliveira, Fernando; Souto, Pedro; Kim, Hyerim; Nakamatsu, Javier
ABSTRACT: Enzyme‐mediated in situ functionalization of cotton fibers was studied using laccase. Caffeic acid and morin were used as reactive phenolic substrates for laccase and further employed to the modification of fiber surfaces. Laccase‐mediated oxidation and polymerization reactions of caffeic acid were monitored by ultraviolet–visible spectroscopy. During the wetting process, initial cationization of fiber surfaces using poly(diallyldimethylammonium chloride) followed by enzymatic treatment with phenolic substrates resulted ineffective polymer grafting evidenced by high color stability. Changes of fiber surface properties by polymer grafting, such as morphology and hydrophilicity/hydrophobicity, were tested using scanning electron microscopy and gravimetric absorption tests. An acceptable level of color resistance to washing stress was obtained on caffeic acid treated samples, and a high level of rubbing resistance was obtained on samples treated with both caffeic acid and morin. Regarding the ultraviolet protection test, the cationized and enzymatically functionalized samples showed a very good protection grade (ultraviolet protection factor = 25). Finally, the antioxidant activity test of the modified fibers presented an improvement for radical scavenging potential due to the phenolic compounds incorporated to cotton fibers by laccase‐mediated catalysis. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 45801. Abstract :